HARD WORK CHARACTER ON NOVEL RADEN MANDASIA SI PENCURI DAGING SAPI BY YUSI AVIANTO PAREANOM - Riza Perdana; Suyitno Suyitno; Herman J. Waluyo (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2019)
Novel is one of literature which full of character education value. The aims of this research describe the character education value of hard work in the novel. The mental hard work of participants in educators have faded and much the mentality to get instant results. This research uses the descriptive qualitative method with source data from novel Raden Mandasia Si Pencuri Daging Sapi by Yusi Avianto Pareanom Banan publisher 2016. Close reading was used to collect the data, then the data was recorded in the form of hard work education data, processing data and analyzing data The results of this research that novel contains a lot of hard-working education values shown by the characters. Figures from this novel are (1) Sungu Lembu, (2) Raden Mandasia, (3) Prabu Watugunung, (4) Loki Tua, (5) Nyai Manggis, (6) Many Wetan, (7) Barja, (8) Wulu Many, (9) Jongkeng, (10) Resi Tama, and (11) Melur. The value of character education of hard work on this novel can be instilled to learners along with related learning. Thus it can assist the educator in determining the proper literary works for the material to grow the character of the hard work of the learners.